Migration in Spain: Historical Background and Current Trends - Olympia Bover; Pilar Velilla (Institute for the Study of Labor (IZA), 1999)
We review the different migration episodes in Spain since the beginning of the 20th century, with special emphasis on the pieces of empirical work that have tried to identify the factors behind them. Migrations abroad for the 1900-1950 and 1950-1973 periods are considered. Foreign immigration is also discussed. Special attention is devoted to internal migration, both to inter-regional and intra-regional flows. Since the early 1980?s net inter-regional flows have fallen and, following the expansion of the welfare state, the traditionally poor and high unemployment regions have become net immigration regions, while the reverse has happened with the better off ones. Intra-regional migration, which has not received much attention so far, is also analysed to understand its spectacular increase in all regions since 1982. This is associated to the increased employment opportunities in the services sector that has prompted moves (mainly within regions), mostly of skilled workers, towards larger towns where the new jobs are.
Keywords: J61; J15; 330; Migration; migration policy; Binnenwanderung; Spanien